Measuring transducers for optical diagnostic system with multifunctional unitary photovoltaic converters - R. I. Vorobei; O. K. Gusev; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky; L. I. Shadurskaya (Приборы и методы измерений, 2018)
Modern measuring transducers for optical diagnostic system should perform automatic parameter estimation of optical signal and automatic switching between different energetic and optical sensitivity ranges. Traditional solution of this problem lies in the field of multi-sensory systems, complex optical schemes and complex signal processing algorithms. The paper aims at the development of new measuring transducers for optical diagnostic system on a basis of multifunctional unitary photovoltaic converters built on semiconductors with low-concentration deep dopants that form multiple energy levels for different charge states in the band gap. Relative complexity of physical processes accompanying the recharge of several energy levels of multiply-charged deep dopant makes it possible to realize the multifunctionality of a photoelectric converter albeit simple sensor design.The proposed unitary photovoltaic converters proved to have extended functional characteristics and increased ranges of energetic characteristic (by dozens dB) and spectral sensitivity characteristic with possible shifts of red margin by 2 to 4 μm in the spectral sensitivity range of 1–10 μm. Energetic and spectral sensitivity characteristic ranges could be switched either by measurement signal itself or by additional control inputs. Possible materials for resistive or barrier photovoltaic converter structure are Germanium, Silicon, А3В5 systems and other semiconductors including that compatible with «non-silicon» technologies and structures on sapphire substrate.